Towards the Integration of Digital Citizenship in Foreign Language Education: concepts, practices and training - Marta Giralt; Silvia Benini; Liam Murray; Christiane Lütge; Yasemin Erdemgil; Claudia Mustroph; Ana Raquel Simões; Susana Senos; Lavinia Bracci; Fiora Biagi; Ireta Čekse; Thorsten Merse (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article reports on different research and pedagogical practices that have been taking place as part of a transnational European Erasmus+ project aiming to strengthen the profile of Digital Citizenship Education (DCE) in the context of Foreign Language Education (FLE). In order to do this, this article briefly reviews some of the key concepts (eg critical digital literacies, democratic cultures) for an evolving definition and (re)conceptualization of digital citizenship in the context of FLE. Equally, a critical analysis of European documents concerning these important topics will be carried out to inform our proposed pedagogical framework, which will be suggested as the grounds for presenting the results of different DCE practices.The first of these practices is the development of resources for teachers to integrate DCE into foreign language learning followed by a training package for teachers. The results collected after piloting one component of the training package-the self-study online course-and the feedback received from the course participants' questionnaire, will be presented and discussed, together with a self-reflection tool for teachers. In addition, some qualitative data results will allow us to explore the perceptions of pre-service teachers regarding the challenges of integrating DCE into FLE. To conclude, some concrete recommendations will be given toward the development and implementation of DCE in foreign language education.